2019
DOI: 10.1002/jclp.22888
|View full text |Cite
|
Sign up to set email alerts
|

Youth's school experience: Testing the role of symptoms of anxiety and co‐occurring symptoms of depression

Abstract: Although symptoms of anxiety often coexist with symptoms of depression, little is known on how such coexistence affects youth's school experiences. Objectives: We tested how the two types of behaviors, when coexisting, were associated with youth's negative attitude toward teachers, school, and poor peer relations. Method: Data were collected from 203 ethnically and socioeconomically diverse youth (male: 24.6%; mean = 15.8 years, standard deviation = 2.4) with the 3rd edition of the Behavioral Assessment for Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(95 reference statements)
0
0
0
Order By: Relevance
“…Higher levels of anxiety, depression and burnout are associated with lower levels of positive suicidal ideation. These results agree with those of previous studies associating suicidal ideation with anxiety, and also with investigations of the relationship of suicidal ideation with burnout, and especially with depressive symptoms [20,21,26,47]. The result confirms our working hypotheses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Higher levels of anxiety, depression and burnout are associated with lower levels of positive suicidal ideation. These results agree with those of previous studies associating suicidal ideation with anxiety, and also with investigations of the relationship of suicidal ideation with burnout, and especially with depressive symptoms [20,21,26,47]. The result confirms our working hypotheses.…”
Section: Discussionsupporting
confidence: 93%
“…Some recent studies have shown the presence of suicidal idea-tion in adolescents even months before university entrance exams [46]. And although suicidal ideation has been associated in different studies with burnout, as we have just seen, as well as with emotional alteration, including anxiety and depression, there are not many studies that have explored this association in students facing the university entrance exam in Spain [26,47]. Hence, we think that it is necessary to study these aspects so that a greater knowledge of these circumstances can help to plan more efficiently initiatives aimed at the prevention of suicide in young people.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation